An Innovative Interprofessional Course in Ophthalmology and Low Vision for Occupational Therapy Students. (March 2023) - Bell, Alison; Bonafede, Lucas; Lorch, Arlene; Snitzer, Melanie; Edmonds, Scott A.; Levin, Alex V.
Introduction: There is an increasing need for occupational therapists with the skills to provide low vision services, however, there is a lack of standardized training of low vision occupational therapy services. The purpose of this study is to design and evaluate a course for occupational therapy students to improve their skills and knowledge about ophthalmology and low vision.Methods: A multifaceted, 15-week curriculum using didactic learning, clinical experience, and reflective writing was created to instruct second-year occupational therapy students in ophthalmology and low vision. Participants included 19 occupational therapy students from Thomas Jefferson University. Each trainee participated in the course modules and then submitted their course evaluations and reflective writings for review. Participants evaluated their satisfaction with the course using a Likert-scale and open-ended comments. Reflective writing from each participant was reviewed by occupational therapy faculty authors (AB, AL).Results: Nineteen students participated in the course, with 19 (100%) of participants reporting being "satisfied" or "highly satisfied" with the course. Analysis of the reflective writings revealed three main themes: the impact of eye-related medical conditions on daily life, insight into the provider-patient interaction and relationship, and the potential role of the occupational therapist on the vision team as an agent to maximize patient adjustment and function.Discussion: This collaborative, multimodal interprofessional educational model can assist in training and sensitizing occupational therapy students in the areas of ophthalmology and low vision.Implications for Practitioners: This report provides a model for medical educators to utilize in the training of occupational therapy students.